Design and Modeling of off-grid DC Micro-grid for DC Homes: Case Study of Lake Ziway Highland (Tullu Gudo Island) - Mati, Oljira (ASTU, 2018)
This thesis presents a design and modeling of off-grid DC micro-grid for DC homes: case study of Ziway lake highland (Tullu Gudo island). The renewable energy sources, such as solar photovoltaic, wind, and other alternate source have huge potential to solve the problem of energy in the rural area of Ethiopia. To provide an economical and sustainable power to rural areas renewable energy systems are very much suitable. The primary goal of this thesis is to design, model and control an energy efficient, sustainable and less expensive off-grid DC micro-grid to promote microgrid application for rural electrification in Ethiopia, and to manage local electricity generation and storage systems. This DC micro-grid has an appropriate bus voltage of DC to supply efficiently a home load. A home load may include the appliances of lighting, TV, mobile charger, tape recorder/radio, refrigerator, and some cooking appliance. MATLAB is used to model and control an off-grid PV source, energy storage system, and distribution network for five (5) DC homes. In this study, design, control and modeling of each component has been accomplished. The validity of the off-grid DC micro-grid is evaluated by using simulations in Simulink software. Compared to the AC model, the power loss is reduced by close to 43% in the DC model, when factoring in standby loss. If standby loss was eliminated from the AC model, DC distribution would still reduce the power loss by almost 21%. The study shows that a 48V off-grid DC micro-grid is effective solution versus the existing AC system. Cost analysis also shows the feasibility of the proposed system as compared to commonly used AC distribution network.
Keywords: DC micro-grid, Energy storage, DC loads, AC system, photovoltaic panel and simulation